Perception and clinical decisions from inflammatory bowel diseases’ specialists towards positioning of new therapies in Crohn's disease and ulcerative colitis: A national web-based survey from the Brazilian IBD study group (GEDIIB) - Romero, Roberta Krause; Magro, Daniela Oliveira; Queiroz, Natalia Sousa Freitas; Damião, Aderson Omar Mourão Cintra; Teixeira, Fabio Vieira; Nones, Rodrigo Bremer; Sassaki, Ligia Yukie [UNESP]; Saad-Hossne, Rogerio [UNESP]; Kotze, Paulo Gustavo (Elsevier, 2021)
Background: In the last decade, new therapies with different mechanisms of action have been approved for the treatment of moderate to severe Crohn's disease (CD) and ulcerative colitis (UC). Due to the lack of comparative head-to-head trials, the ideal positioning of agents as the most appropriate first- or second-line therapies remains to be defined. Objective: This survey aimed to evaluate the perception and decisions of Brazilian Inflammatory Bowel Diseases (IBD) specialists in positioning of new therapies (vedolizumab [VEDO], ustekinumab [UST] and tofacitinib [TOFA]) in the management of IBD in different clinical scenarios. Methodology: An anonymous national web-based questionnaire was used to determine the positioning of treatment options in different clinical scenarios (using Google Forms platform), which involved different age ranges, phenotypes, clinical situations and previous exposure to anti-TNF agents (14 scenarios for CD and 10 scenarios for UC). In CD, physicians could choose between UST or VEDO, whilst in UC, between UST, VEDO or TOFA. Six reasons for the specific choice were proposed, such as mechanism of action, safety, method of administration or onset of action. Statistical analysis was carried out with chi-square and t-tests. Results: A total of 150 out of 672 GEDIIB IBD specialists (22.32%) responded to the survey. In CD scenarios, UST was the most dominant choice (11/14 scenarios), with VEDO dominating only 3 clinical situations. In UC scenarios, VEDO was the dominant choice (8/10), with UST being chosen for scenarios that included extraintestinal manifestations. Among the reasons for specific choices, the most commonly chosen were the higher efficacy due to the intrinsic mechanism of action and safety profile. Conclusions: UST was the dominant choice as compared to VEDO in CD in most scenarios, especially due to its mechanism of action and safety. VEDO was the dominant choice as compared to UST and TOFA in UC scenarios, mainly for reasons also related to its mechanism of action and safety profile. Comparative studies including patient outcomes are needed to better define the positioning of new IBD therapeutic options in our country.
Percepción y decisiones clínicas de especialistas en enfermedades inflamatorias intestinales hacia el posicionamiento de nuevas terapias en la enfermedad de Crohn y la colitis ulcerosa: una encuesta web de práctica clínica nacional del Grupo de Estudios Brasileño de Enfermedades Inflamatorias (GEDIIB)
Keywords: Biological products; Crohn's disease; Integrins; Janus kinase inhibitors; Ulcerative colitis; Ustekinumab